Correlation of structure and function in glaucoma - Maria Joanna Rodriguez-Chan, MD; Patricia M. Khu,MD,MS; Ma. Margarita L. Luna, MD; Manuel B. Agulto, MD (Philippine Journal of Ophthalmology)
Objective: This study assessed the relationship of two structural tests, optic-disc photography and optical coherence tomography (OCT), and a functional test, standard achromatic perimetry (SAP), in the diagnosis of glaucoma.